2008
DOI: 10.1111/j.1532-849x.2008.00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Shade‐Matching Abilities of Dental Laboratory Technicians Using a Commercial Light Source

Abstract: Purpose: The purpose of this study was to evaluate dental laboratory technicians' abilities to match shades using a light-corrective device under conventional laboratory conditions. The variables measured were years experience, gender, and light source. Materials and Methods: A 14-item shade-matching quiz (SMQ) was field-tested and deemed adequate. Information included age, gender, number of years experience, and Ishihara's Colour-Blindness Assessment. Forty-two dental technicians from five northeast Ohio labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 12 publications
3
56
0
4
Order By: Relevance
“…Renk seçiminin yapıldığı muayenehane ve laboratuvarlar, yaklaşık olarak 5500K renk sıcaklığına sahip olmalı ve >90 CRI (Color Rendering Index) sahip kontrollü ışık kaynakları kullanmalıdır. 10,11,17 Bazı araştırmacılar farklı ışık kaynaklarının klinikte renk eşleştirmeye herhangi bir etkisi olmadığını söylerken 1,14,18 başka bir araştırmacı ise ışık kaynağı yoğunluğunun renk seçimine önemli bir etkisi olmadığını belirtmiştir. 11 Çalışmamızda kullanılan TTB'a ait olan ışık kaynağının özellikleri renk sıcaklık değeri 5500 K, 1500 lux / 140 footcandle ışık yoğunluğuna sahiptir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Renk seçiminin yapıldığı muayenehane ve laboratuvarlar, yaklaşık olarak 5500K renk sıcaklığına sahip olmalı ve >90 CRI (Color Rendering Index) sahip kontrollü ışık kaynakları kullanmalıdır. 10,11,17 Bazı araştırmacılar farklı ışık kaynaklarının klinikte renk eşleştirmeye herhangi bir etkisi olmadığını söylerken 1,14,18 başka bir araştırmacı ise ışık kaynağı yoğunluğunun renk seçimine önemli bir etkisi olmadığını belirtmiştir. 11 Çalışmamızda kullanılan TTB'a ait olan ışık kaynağının özellikleri renk sıcaklık değeri 5500 K, 1500 lux / 140 footcandle ışık yoğunluğuna sahiptir.…”
Section: Discussionunclassified
“…30 Bunula birlikte, diş hekimlerinin renk probleminin üstesinden gelebilmeleri için eğitim yönünden donatılmadıklarını, görsel fizyoloji veya renk bilimi hakkında çok az eğitimli ya da eğitimsiz olduklarını, ayrıca diş hekimliği okullarında renk konusunda eğitim verilse de bunun yüzeysel veya basitleştirilmiş olduğunu belirtmişlerdir. 31 Mesleki tecrübenin ve renk kavramlarıyla ilgili özel bilgilere sahip olmanın renk seçiminde başarıyı arttırdığını bildiren araştırmacılar olduğu gibi, 1,13,23,25,26,32 hiç bir etkisinin olmadığını iddia eden araştırmacılar 14,18,27,[33][34][35][36] ile renk eş-leştirmedeki becerinin egzersizlerle ve renk kavramlarıyla ilgili eğitimlerle geliştirilebileceğini savunan araştırmacılar da vardır. 11,23,37,38 Bizim çalışmamızda ise; tecrübeyle birlikte renk eşleştirme başarısının arttığı ve ayrıca renk kavramları ve renk eşleştirme prosedürleri hakkında eğitimli olmanın renk seçimine etkisi olduğu görülmektedir.…”
Section: Discussionunclassified
“…3 Studies that involved dental students and professionals reported percentage of color deficient males (6-14%) similar to the findings for general male population. [4][5][6][7][8][9][10] As far as color normal persons of both genders are concerned, vision science literature stated that differences between color normal men and women in red-green color discrimination were not significant if color deficient males and females and heterozygote female carriers (15%) were excluded from comparisons. 11 When color assessment and diagnosis test was performed on 150 color normal males and the same number of color normal females, no significant gender-related difference was recorded.…”
Section: Introductionmentioning
confidence: 99%
“…DOI: 10.9790/0853-150903101105 www.iosrjournals.org 105 | Page reproducibility is often achieved as a result of the skill of the dental technician and an appropriate environment for fabrication, and the ability to reproduce the color of the target shade is likely to differ among laboratories [15,22]. The lack of significance in this study might be a result of having ∆E* values lower than 3.7, because values below 3.7 were considered to be clinically acceptable [26].…”
Section: Factors Affecting Color Reproducibility Of Resin-veneered Prmentioning
confidence: 99%
“…[20,21] This relates not only to the artistic skill of the dental technician, but also to the dental laboratory in which the technician works [15], including its equipment, the materials available, the environment, and working conditions and wages. Generally, dental technicians' shade-matching abilities improve under lightcorrective devices compared with conventional laboratory lighting conditions [22,23]. For adequate shade matching, relevant uncovered costs are needed for dental laboratories [24].…”
Section: Introductionmentioning
confidence: 99%